I-search, you search, we all learn to research a how-to-do-it manual for teaching elementary school students to solve information problems - Duncan, Donna; Lockhart, Laura (New York Neal-Schuman Publishers, 2000)
"This manual introduces teachers and librarians to strategies to get students to move away from traditional research in which they merely restate information to a higher order of thinking. . . . Along the way, they will learn about choosing topics, evaluating sources, note taking, presenting findings, and working with peers to develop better skills."--SLJ.
Section I What Do I Want to Know? -- Choosing the Topic 3 -- Lesson: Introducing the I-Search Project 4 -- Learning Log 16 -- Skimming and Scanning 18 -- Library Skills 19 -- Lesson: Why I Chose This Topic 22 -- Developing Questions 27 -- What I Knew Before I Started My I-Search 28 -- Lesson: What I Knew Before I Started My I-Search 29 -- Higher-Level Questions 32 -- Lesson: Higher-Level Questions 32 -- Creating I-Search Questions 35 -- Lesson: Creating I-Search Questions 37 -- Organize and Make a Plan for Research 40 -- Lesson: Make a Research Planner 41 -- Section II Where Can I Find the Answers to My Questions? -- Finding Sources and Experts 49 -- Brainstorm Sources 49 -- Interviews 51 -- Lesson: Conducting an Interview 53 -- Section III How Will I Record the Information That I Find? -- Taking Notes and Citing Sources 63 -- Lesson: Notetaking and Citing Sources 65 -- Search 73 -- Search Log 74 -- Lesson: The Search Log 76 -- Location and Access of Sources 77 -- Lesson: Locating Sources 79 -- Section IV How Will I Show What I Learned? -- Writing the I-Search Paper 87 -- Writing the I-Search Paper 88 -- Lesson: Why I Chose This Topic (Day One) 89 -- Lesson: Why I Chose This Topic (Day Two) 93 -- Peer Conferencing 94 -- Lesson: Peer Conferencing 94 -- Writing Process for the Remainder of the Paper 100 -- Components of the Self-Directed Writing Sessions 100 -- Lesson: Writing The Search 101 -- What I Learned 102 -- Lesson: Writing the First Draft of What I Learned 103 -- Final Copies 105 -- Developing and Presenting the I-Search Project 107 -- Choosing an I-Search Project 108 -- Developing a Rubric for the Products 109 -- Designing the Product 109 -- I-Search Project Contracts 110 -- Presenting the I-Search Project and Developing Communication Skills 110 -- Lesson: Introduction and Eye Contact 112 -- Lesson: Speaking Clearly (Diction) and Volume 114 -- Lesson: Posture and Gestures 115 -- Lesson: Organization 116 -- Communication Skills Rubric 119 -- Presentation Days 119 -- Section V How Will I Know I Did a Good Job? -- Teacher and Student Assessment and Evaluation 123 -- Lesson: Developing the I-Search Paper Rubric 125 -- I-Search Project Rubrics 129 -- Communication Rubric 131 -- Student Self Evaluation 133 -- Scoring the Rubrics 133 -- Other Assessments and Evaluations 133 -- Appendix Student I-Search Papers 139 -- Sarah Dickerson 139 -- Emily Laquitara 141 -- Lori Wojciechowski 143 -- Cynthia Gayton 145 -- Wendi Youngblood 146 -- Courtney Wagner 149 -- Justin McLearen 151 -- Emily Cleveland 153.
Includes index.
Includes bibliographical references and index.
Keywords: Library orientation for school children -- United States; Report writing